Penggunaan Metode Economic Order Quantity dan Least Square Pada Aplikasi Prediksi Peramalan Obat Berbasis Web - Benny Danendra Hadi; Henni Endah Wahanni; Fawwaz Ali Akbar (Lembaga Pengembangan Kinerja Dosen, 2025)
Ensuring the availability of drugs and preserving the standard of health care services depend on effective pharmaceutical inventory management. Manual inventory management at Klinik Pratama dr. Vitis Grogol, Kab. Kediri, causes a number of common issues including overstocking or stockouts, erratic demand patterns, and inaccurate purchase quantities. This research aims to address these problems by predicting drug demand using one year of prior sales data via the Least Squares method and calculating the ideal order quantity, including reorder points and safety stock, using the Economic Order Quantity (EOQ) model. Incorporating these techniques into a Pharmacy Information System (SIA) should produce a more orderly and efficient inventory control system. The suggested strategy should improve the accuracy of inventory planning, ensure fast medication availability, and eventually enhance patient care and operational efficiency at the clinic.